Antispeciesist feminisms in Ecuador and Colombia: Queer practices and decolonial veganisms - Ponce-León, Juan José (2024)
This article analyzes the configuration of anti-speciesist feminisms (AF) based on the experiences of a trans activist and twelve animalist women from Ecuador, along with the performative work of a trans artist from Colombia. A theoretical model is used that puts community feminisms in dialogue with Feminist Animal Studies to identify the decolonial discourses and practices that characterize these political subjectivities. Qualitative methodology based on fourteen in-depth interviews and the analysis of images coded with the Atlas.ti program is used. On the one hand, we show how activists denounce patriarchal and carnist regimes within social movements and, on the other hand, we emphasize the place of the body-territory and animality as a sensitive space of political dispute to question gender and species binarisms. Through reanimalization as a decolonial practice, which entails embodying certain politics of the abject through “animal transvestism”, the close link between speciesism and the coloniality of power and gender becomes evident. It is concluded that these anti-speciesist feminisms question the place of the animal as a marker of power and as a process of subalternization and, through performance, seek to translate the suffering place of non-human animals to promote interspecies alliances and fabrics.